Shifting sands : searching for a compromise in the WTO negotiations on agriculture - Peters, Ralf (UN New YorkUS, 2004)
Provides a rigorous quantitative assessment of various options being discussed in the WTO agriculture negotiations. Focuses on the Framework for Establishing Modalities in Agriculture. Uses a computable global trade model viz, the Agriculture Trade Policy Simulation Model (ATPSM). Seeks to show that a trade model can be used to assist in the preparation and evaluating negotiating positions.